KAJIAN PENGARUH TEKNIK PEMBUATAN LUBANG TERHADAP KEKUATAN TARIK KOMPOSIT HIBRID SERAT GELAS DAN SERAT KARUNG PLASTIK - Kuncoro Diharjo (Faculty of Industrial Technology Universitas Islam Indonesia, 2006)
In panels or components, there are holes for joinning with other part. There are two method for manufacturing a hole, i.e. by boring and molding processes. The objective of this research is to investigate the effect of hole manufacturing method on the tensile properties of hybride composite reinforced chopped strand mat of E-glass fiber and woven roving fiber of plastic bag. The materials in this research are plastic bag fiber, chopped strand mat of E-glass fiber (300 gr/m2), unsaturated polyester 157 BQTN-EX, and MEKPO hardener. The composite was made using press mold method, prepared with 4 laminates of glass fiber and 3 laminates of plastic bag fiber. The weight fraction fiber (Wf) of the composite was around 38%. The tensile test specimens were produced according to ASTM D 5766. In the middle of each specimen, there is a hole with 4, 6, or 8 mm in diameter. There are two types hole, i.e. holes were manufactured using boring and molding process methods. The result shows that the highest tensile strength of the composites occurs on the composite with 6 mm in diameter of hole manufactured by boring and molding process. It can be recommended that composite has the higher strength for 6 mm in diameter of hole for joining. The composites with 4 and 6 diameters of holes manufactured by molding process have higher tensile strength compared to that manufactured by boring process. In contrast, the tensile strength of the composite with 8 mm in diameter of hole produced by boring is higher than that of the composite with 8 mm in diameter of hole produced by molding process.Keywords : plastic bag fiber, E-glass fiber, molding process, boring.